Minimally Invasive Modified Nuss Procedure for Repair of Pectus Excavatum in Pediatric Patients: Single-Centre Retrospective Observational Study - Miro Jukić; Ivan Mustapić; Tomislav Šušnjar; Zenon Pogorelić (MDPI AG, 2021)
Background: The treatment of pectus excavatum can be conservative or surgical. The aim of this study was to determine the factors influencing the outcomes of treatment after a minimally invasive Nuss corrective surgery procedure in pediatric patients. Methods: A total of 30 patient who underwent a minimally invasive Nuss corrective procedure for pectus excavatum from 1 January 2014 to 31 December 2020 were included in thisretrospective study. The collected data included thepatient's demographic characteristics (age, sex, height, weight, body mass index-BMI, Haller index), treatment outcomes (duration of surgery, length of hospital stay, intraoperative complications, early and late complications, postoperative analgesia), and overall patient and legal guardian satisfaction two years after the procedure. Results: A total of 22 male and 8 female patients were included in the study. The median age was 15 years (interquartile range-IQR 14, 16), and the median BMI was 18.5 kg/m2 (IQR 17.7, 20.4) and 18.2 kg/m2 (IQR 16.9, 18.6) for males and females, respectively. The median CT Haller index was 3.67 (IQR 3.48, 4.09) for male and 3.69 (IQR 3.45, 3.9) for female patients. The median surgery duration was 120 min (IQR 100, 130), and the median hospital stay length was 8.5 days (IQR 8, 9.75). Indications for surgery were psychological (47%), followed by respiratory (30%) and combined respiratory-cardiac (20%) and respiratory-psychological disorders (3%). Early complications were observed in 18 patients (60%), and late complications were observed in 7 patients (23.3%). Intraoperative complications were not recorded. The most common early complications were pneumothorax and subcutaneous emphysema (30%), while late complications included bar displacement (10%) and deformity recurrence (6.6%). Overall, the procedure was successful in 93.1% of patients. Upon arrival home, 22 patients (81.5%) used analgesics for at least one day, up to a maximum of six months. A total of 23 (76.7%) operated patients determined that the surgical procedure had excellent results (grade 5), 4 (13.3%) patients report a good result (grade 4), 1(3.3%) patient reported a mediocre result, and one patient (3.3%) reported a bad result (grades 3 and 2, respectively). Conclusion: The Nuss procedure is a safe and effective method for treating funnel chest in children and adolescents. It also providesexcellent cosmetic and aesthetic results as well as subjective satisfaction with the outcome of surgical treatment.